A Stochastic View on the Effect of Random Rail Irregularities on Railway Bridge Vibrations. Issue 12 (2nd December 2019) - Salcher, Patrick; Adam, Christoph; Kuisle, Anna
Abstract: This contribution studies dynamic amplification factors that consider the impact of random rail irregularities on the deflection and acceleration response of simple railway bridges. Response statistics for a set of plane fully coupled bridge–vehicle interaction models with random irregularity profiles are derived by Monte Carlo simulations. The underlying samples of random irregularity profiles are generated from a power spectral density function, assuming that the uneven rail surface is governed by a Gaussian stochastic process in space. A modified bootstrap method is used to identify the required sample size of profiles for sufficiently accurate description of the random response. On the basis of this pilot study, a parametric response examination of short span railway bridges with variable length, fundamental frequency, structural mass and damping, and track quality in a range commonly observed in real structures is conducted. A statistical representation of the uncertain bridge response is employed for analytical modelling of the response amplification due to random rail irregularities considering limit state-based exceedance probabilities. The results are compared to outcomes of existing simplified approaches in design codes used to take into account the effect of rail irregularities on the dynamic bridge response, showing the improvement of the developed framework.